2023
DOI: 10.29122/mipi.v15i2.4769
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic and Boussinesq Wave Modeling for the N219 Amphibious Aircraft Seaplane Dock Development Plan in Panjang Island

Abstract: The flight test of N219 Amphibious aircraft will be targeted in 2003/2024. For flight tests, these aircraft need a seaplane dock. One of the potential locations for the seaplane dock is Panjang Island at Seribu Islands. This study aims to know the characteristic of hydrodynamic and wave conditions and to determine whether Panjang Island is suitable for the seaplane dock. This study uses a modeling method with MIKE 21 FM HD-SW module and MIKE 21 Boussinesq Wave (BW)  module. The bathymetry data were obtained fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…The role of the BW-type model has been reported by [22] when simulating wave propagation in Panjang Island incorporating manning variations between 10 and 32 m 1/3 s -1 . In their study, it is suggested to utilize a combination of hydro, wave, and littoral transport/sedimentation models to assess the possibility of changes in the site's bed level and bathymetry before running the BW model.…”
Section: Figure 1 Modeling Domain Area In Kedungsepur Areamentioning
confidence: 99%
“…The role of the BW-type model has been reported by [22] when simulating wave propagation in Panjang Island incorporating manning variations between 10 and 32 m 1/3 s -1 . In their study, it is suggested to utilize a combination of hydro, wave, and littoral transport/sedimentation models to assess the possibility of changes in the site's bed level and bathymetry before running the BW model.…”
Section: Figure 1 Modeling Domain Area In Kedungsepur Areamentioning
confidence: 99%
“…Based on the modeling results, the validation value between the tidal driver model (TMD) data and MIKE 21 HD is 92 %. Thermal dispersion modeling has also been carried out around the Muara Karang PLTU using three-dimensional MIKE 3 Flow Model Flexible Mesh (Khoirunnisa et al, 2021b). Based on research conducted by Saputra (2018), the current velocity in the master plan condition is smaller than the post-reclamation condition; this is due to the deflection of the current in the reclamation island (Saputra, 2018).…”
Section: Introductionmentioning
confidence: 99%